Islets Transplantation at a Crossroads - Need for Urgent Regulatory Update in the United States: Perspective Presented During the Scientific Sessions 2021 at the American Diabetes Association Congress - Witkowski, Piotr; Philipson, Louis H.; Buse, John B.; Robertson, R. Paul; Alejandro, Rodolfo; Bellin, Melena D.; Kandeel, Fouad; Baidal, David; Gaglia, Jason L.; Posselt, Andrew M.; Anteby, Roi; Bachul, Piotr J.; et al. (Frontiers in Endocrinology, 2022)
Clinical islet allotransplantation has been successfully regulated as tissue/organs for transplantation and recognized worldwide as a safe and efficacious therapy for selected patients with type 1 diabetes mellitus. However, in the United States, the FDA has considered pancreatic islets as biologic drugs, and islet transplantation has not yet shifted from the experimental to the clinical for last 20 years. A recent Biological License Application for human islets submitted by a private company and a subsequent FDA report uncovered major deficiencies in current regulations of human islets, which are deeply concerning regarding patient safety and efficacy. Despite the application of drug manufacturing technology and regulations, the final islet product sterility and potency cannot be confirmed, even when islets meet all the predetermined release criteria. Therefore, further regulation of islets as drugs is obsolete and will continue to hinder clinical application of islet transplantation in the US. The Organ Procurement and Transplantation Network together with the United Network for Organ Sharing developed a separate from the FDA regulatory framework under Human Resources & Services Administration, to assure safety and efficacy of transplantation. Based on similar biologic characteristics of islets and human organs, we propose inclusion of islets into the existing regulatory framework for organs for transplantation, along with continued FDA oversight for islet processing, as for other cell/tissue products exempt from BLA. It would reassure islet quality, efficacy and access for Americans with diabetes to safe and effective islet transplantation.